LITERATURE REVIEWS: THE INFLUENCE OF STUDENT MOTIVATION ON LEARNING IN VOCATIONAL EDUCATION - Raditya Fardiansyah; Suci Hastika Damayanti; Bambang Darmawan (Journal of Logistics and Supply Chain, 2021)
Background: Student motivation is one of the factors that influence the quality of learning, the high level of motivation will create a good quality learning process. Purpose: this study aims to determine how much influence student motivation has on the learning process in vocational education. Method: literature study from 2010 to 2020. Data obtained from the Science and Technology Index database with the keywords vocational, vocational education, motivation. Result: Through the presented problems in Problem-Based Learning, students can become more engaged in efforts to solve issues and participate in utilizing critical thinking skills. With the presence of the EFI Scanner, students' learning motivation averages at 82.31%. From the assessment of students' learning motivation, a perseverance and determination score of 88.65% was achieved. The use of animation media in delivering electrical system materials provides higher motivation compared to using PowerPoint media. Motivation features developed with the Pre-defined set approach have a more effective impact on improving learning achievements. Conclusion: The Problem-Based Learning approach, EFI Scanner, Animation Media, and Pre-defined set have a positive influence on student learning outcomes, critical thinking skills, learning motivation, and academic achievements.